Resistência para viver: as estratégias da condição humana a partir de vidas secas, em seus horizontes de transendência - Braga, Hermide Menquini (2006)
Resistance to live: the strategies of the human condition in Vidas Secas , within its horizons of transcendence is a work based on the drama Vidas Secas , by Graciliano Ramos. It caught our attention for showing some tension between the attachment to life and the difficulties to obtain the primary resources for maintenance. The organization of societies and the élan that moves men toward intellectual development cause resistance to live. On the literary analysis of the book we shall emphasize the characteristics of each character and the close relations among Fabiano s family members, who present identical signs of social retreat, boldly shown by the difficulty of verbal expression. The content of the novel sends these characters to the big city, a place where they expose their inadequacy. This reality becomes cruel when Fabiano, the cowboy, suffers material harm due to hi9s lack of argument, not because of intellectual inability, but mainly because of the subordinate position demanded by his living situation, settled in his boss land. Through the analysis of the structures of Christian anthropology, it is possible to understand the strategies of men s spirit to keep living. The flow that connects human life to outer world and the transcendence give us examples of hope coming from our comprehension about what the mankind is. Supported by Henrique C. L. Vaz theory of Philosophical Anthropology, by Alfredo Bosi s notions of resistance literature, and still some knowledge about metaphor philosophy from Franklin Leopoldo e Silva s study of Bergonian thought, the notion of irony in Graciliano s book is understood. This resistant porture links the text Vidas Secas to Socrates dialectic. This opposition between life and death, dryness and flood, understanding and alienation, enhances human communication capability with the exterior and with the transcendental life. It identifies the natural mysticism and the Christian mysticism, which are different but progressive stages in human clarification.